DRG system in the Czech Republic and its implications - Kučera, Dušan (2017)
The aim of this thesis is to provide an overview of the Czech healthcare system, with focus on specialities of the healthcare product and market, describing different factors that play a role in the process. Main focus will be put on payment schemes for hospital care according to different approaches. The theoretical part will provide necessary tools to analyse the dataset in the practical part. The goal is to analyse the remuneration data from 3 different diagnosis and check for structural changes in the healthcare provision after the payment scheme was changed and the DRG was implemented. However, mainly statistical and economical description of the data will take place, I will include some medical explanations to broaden the reach of the work and analyse the dataset from different approach. The conclusion will be an answer to the question, how the DRG system changes the structure of healthcare and whether the change is beneficial both for the system and for the patients.